Marxism in History of Socialist Movement in Russia: Concept of Viktor Chernov - O. V. Konovalova; A. P. Dvoretskaya; L. V. Belgorodskaya (Научный диалог)
This article explores the evolution of the views held by Viktor Chernov, a leader and theorist of the Socialist Revolutionary Party, regarding the role of Marxism in the development of the socialist movement in Russia from the late 19th century to the early third of the 20th century. The study reveals Chernov’s relationship with the ideological and theoretical legacy of Marxism, offering a fresh perspective on its achievements and shortcomings. The sources include both published and unpublished works of the theorist of the Socialist Revolutionary movement. The authors conclude that Chernov’s views on the role and significance of Marxism in the history of socio-political thought and activism were not static. It is demonstrated that, in the context of polemics with Russian Social Democrats prior to World War I, Chernov focused on the philosophical and sociological constructs of Marxism, while also initiating discussions on agrarian issues. Notably, during World War I, he critically assessed Marxism’s stance on national relations. Furthermore, it is revealed that in the 1930s, he linked the rise of National Socialists in Germany and the consolidation of Stalin’s regime in the USSR to the errors and miscalculations of Marxism. The novelty of this research lies in its contribution to a deeper understanding of Viktor Chernov’s evolving perspectives on the role of Marxism in the history of the socialist movement.